Effects of disc peg drum parameters on maize shelling performance of an axial flow shelling unit - Pachanawan, A.; Doungpueng, K.; Chuan-Udom, S. (International Journal of Agricultural Technology, 2021)
Reserch finding showed that an increase in guide vane inclination and rotor speed resulted in increased maize shelling efficiency and decreased total loss, whereas feed rate and moisture content did not statistically affect shelling efficiency or total loss. A higher moisture content resulted in increased grain breakage while rotor speed, feed rate, and guide vane inclination did not statistically affect grain breakage. A higher moisture content, guide vane inclination, feed rate, and rotor speed tended to increase power consumption. Meanwhile, a higher moisture content, guide vane inclination, and rotor speed tended to increase specific energy consumption whereas an increased feed rate tended to reduce it. Optimal parameters of the drum were a moisture content of less than 17 %wb, a feed rate of less than 2 tons/hr, a guide vane inclination of more than 87 degrees, and a rotor speed of more than 12 m/s.